2015
DOI: 10.1007/s10068-015-0146-4
|View full text |Cite
|
Sign up to set email alerts
|

β-Glucan from Aureobasidum species inhibits fat accumulation in 3T3-L1 adipocyte differentiation

Abstract: The anti-fat accumulative effects of bacteriaderived β-glucan in 3T3-L1 adipocyte differentiation was investigated. 3T3-L1 preadipocytes were treated with β-glucan at 50 and 100 µg/mL during adipogenesis. Oil Red O staining was used to study expressions of the adipogenic genes PPARγ, ACC, and aP2. Adipogenesis of 3T3-L1 cells treated with β-glucan at 50 and 100 µg/mL was significantly (p<0.05) inhibited by 32.8 and 39.7%, respectively, compared with controls. Expressions of the PPARγ gene from 3T3-L1 cells tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Similarly, bacterial β-glucan from Aureobasidium sp. inhibited adipogenesis in 3T3-L1 adipocytes by decreasing the expression of PPARγ, acetyl-CoA carboxylase (ACC), and FABP4 (aP2) genes [ 33 ]. Based on the quantitative RT-PCR results, the β-glucan-FBR extracts strongly inhibited adipogenesis in 3T3-L1 adipocytes.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, bacterial β-glucan from Aureobasidium sp. inhibited adipogenesis in 3T3-L1 adipocytes by decreasing the expression of PPARγ, acetyl-CoA carboxylase (ACC), and FABP4 (aP2) genes [ 33 ]. Based on the quantitative RT-PCR results, the β-glucan-FBR extracts strongly inhibited adipogenesis in 3T3-L1 adipocytes.…”
Section: Resultsmentioning
confidence: 99%
“…To combat against obesity, many research investigators have identi ed molecules or compounds that inhibit adipogenesis. Among those, b-glucan, a polymer of b-glucoses that link through b-(1®3) glycosidic bonds and found in the cell walls of yeast, fungi and some seaweeds, has been shown to inhibit adipogenesis [8][9][10] . Noticeably, a previous study demonstrated that yeast-derived insoluble β-1,3-glucan strongly inhibited adipogenesis better than soluble β-1,3-glucan 11 .…”
Section: Introductionmentioning
confidence: 99%